Health and exposures of United Kingdom Gulf war veterans. Part I: The pattern and extent of ill health. Issue 5 (1st May 2001) - Cherry, N; Creed, F; Silman, A; Dunn, G; Baxter, D; Smedley, J; Taylor, S; Macfarlane, G J
Abstract : OBJECTIVES: To assess the health of United Kingdom Gulf war veterans, to compare their health to that of similar personnel not deployed, to describe patterns of ill health in both groups, and to estimate their extent. METHODS: Main Gulf (n=4795) and validation Gulf (n=4793) cohorts were randomly selected within strata from the population deployed to the Gulf and a non-Gulf cohort (n=4790) from those who were not sent. Seven years after the war subjects completed a questionnaire about their health in the past month, including 95 symptom questions and two manikins on which to shade areas of pain or numbness and tingling. Responses were subjected to a principal component analysis with rotation and to a cluster analysis within each cohort. Mean symptom score was used as a measure of severity. Areas shaded on the manikins were coded to indicate widespread pain and possible toxic neuropathy. RESULTS: A response of 85.5% was achieved. Those who had been to the Gulf were more troubled by every symptom with a mean severity score (3.0) substantially greater than in the non-Gulf cohort (1.7). Seven factors were extracted accounting for 48% of the variance. The scores on five factors (labelled psychological, peripheral, respiratory, gastrointestinal, and concentration) were significantly worse in those who had been to the Gulf. Symptoms suggestive of peripheral neuropathy were found more often (12.5%) in the Gulf than the non-Gulf (6.8%) cohorts. Widespread pain was also found more often (12.2% Gulf; 6.5% non-Gulf). Those who had been to the Gulf were found disproportionately (23.8%) in three clusters with high mean severity scores; only 9.8% of non-Gulf respondents were in these clusters. There was no evidence of an important excess in the use of alcohol, tobacco, or referral to hospital specialists by those who had been to the Gulf. For the same level of reported ill health those who had been to the Gulf were less likely to be referred to specialists than non-Gulf veterans. CONCLUSION: 7 Years after the war, the Gulf war veterans were more troubled about their health than those who had not been sent, with a substantial subgroup reporting a pattern of symptoms suggestive of a significant decline in health.